ANALISIS KOMPARASI PENYELESAIAN SENGKETA HASIL PEMILIHAN UMUM MENURUT HUKUM YANG BERLAKU DI NEGARA INDONESIA DENGAN NEGARA MALAYSIA: Comparative Analysis of Dispute Resolution of General Election Results According to the Laws Applicable in Indonesia and Malaysia - Dewi Aisyah; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2025)
Each country has different mechanisms for resolving election dispute results. The identification of the problem in this research is the comparison of election dispute resolution mechanisms in Indonesia and Malaysia to identify similarities, differences, advantages, and disadvantages. The research employs a normative legal method with a descriptive approach, utilizing secondary data through literature study. Data analysis is qualitative, with conclusions drawn deductively. Based on the research results and conclusions, it is concluded that both Indonesia and Malaysia have special institutions to handle election disputes, namely the Constitutional Court in Indonesia and the High Court in Malaysia. The main difference lies in the availability of legal remedies in Malaysia, while Indonesia does not have this. Indonesia’s advantage is a more detailed trial process regulation, whereas Malaysia’s advantage is a longer filing period allowing for the collection of more relevant evidence.